"Carbon Management": Opportunities and risks for ambitious climate policy - Felix Schenuit; Miranda Böttcher; Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2023)
Climate policy in the European Union (EU) and Germany changed significantly with the adoption of net-zero emissions targets. A key new development is the growing importance of carbon management. The umbrella term includes not only the capture and storage of CO2 (carbon capture and storage, CCS), but also CO2 capture and utilisation (carbon capture and utilisation, CCU) as well as the removal of CO2 from the atmosphere (carbon dioxide removal, CDR). It is important to provide clarity when differentiating between these approaches and identifying their relation to so-called residual emissions and hard-to-abate emissions. This is particularly important because it will determine the overall ambition of climate policy as well as shape future policy designs and their distributional impacts. Current policy and legislative processes should ensure that carbon management does not delay the phase-out of fossil fuels. New policy initiatives present an opportunity to actively shape the interface between ambitious climate and industrial policy.
Keywords: 320; Carbon Management; Carbon Capture and Storage; CCS; Carbon Capture and Utilization; CCU; Carbon Dioxide Removal; CDR; BECCS; DACCS; residual emissions; hard-to-abate emmission; Net Zero Industry Act; Carbon Dioxide Removal; climate policy; climate protection; net-zero target; net-negative emissions